Efektivitas Media Pembelajaran dalam Meningkatkan Pemahaman Materi Perkalian di Sekolah Dasar - Elfiza Elfiza; Darma Nuraini; Adrias Adrias; Fadila Suciana (Bilangan : Jurnal Ilmiah Matematika, Kebumian dan Angkasa, 2025)
This study aims to examine the effectiveness of using instructional media in enhancing the understanding of multiplication concepts in elementary schools. The research employs a library research method. The findings indicate that the use of instructional media in teaching multiplication in elementary schools is significantly more effective compared to conventional methods without media. Media such as Powtoon, PAKALILO (Papan Perkalian Kelinci Lompat), Papan BAPER (Batang Perkalian), and multiplication pockets based on the Indonesian Realistic Mathematics Education (PMRI) approach significantly improve students' understanding of multiplication concepts.